Roça como marca registrada no Brasil: novos significados do rural brasileiro - Silveira, Lidiane Nunes da (2019)
This article searched to identify changes in the meanings of the term roça in Brazil by analyzing 325 brands between 1965 and 2014, using frequency, lexical-syntactic and categorical content analysis (Bardin, 1977). It was observed the extension of meanings, initially of agricultural production and countryside, to nature, nostalgia and sophistication, and, more recently, tradition and regionalisms. These changes of meanings of the term roça reflect the transformations in the Brazilian rural, essentially agricultural in the 1960s, multifunctional in the years 2000. It is suggested that roça could be used to think about rural in Brazil as a category of thought.